EFEKTIFITAS VIDEO TERHADAP PENINGKATAN PENGETAHUAN IBU NIFAS TENTANG TEKNIK MENYUSUI YANG BENAR DI WILAYAH KABUPATEN BANJARNEGARA - Dian Nirmala Sari; Umi Nur Fajri (Jurnal Ilmiah Medsains, 2021)
One of the factors that influence the low coverage of breastfeeding is inappropriate breastfeeding technique. Lack of knowledge and wrong perceptions about how to breastfeed is one of the factors causing problems in breastfeeding. Therefore, a method is needed to increase knowledge of postpartum mothers, namely using Information Counseling Education on correct breastfeeding techniques using videos. The purpose of the study was to determine the effectiveness of video as an IEC medium for increasing mother's knowledge about correct breastfeeding techniques. Quasy experimental research method with pretest post test control group design. The population in this study were all postpartum mothers in Banjarnegara 2 Health Center, Madukara 2 Health Center and Banjarmangu Health Center 2. The sample in this study were postpartum mothers in May – July at the Banjarnegara 2 Health Center, Madukara 2 Health Center and Banjarmangu Health Center 2. Sampling technique with consecutive sampling. The results of the independent t test statistical test showed a p value of 0.185 which means that there is no difference in knowledge between the control and intervention groups. Suggestions for health workers in carrying out midwifery care, especially providing education, can use media so that information will be more easily understood by patients.